Peran dan Kontribusi Nashiruddin Al-Albani (W.1998) dalam Perkembangan Ilmu Hadis - Syarifah, Umaiyatus (RIWAYAH, 2015)
In the thought of contemporary hadith, Muhammad Nashiruddin al Albani is one of hadith ulama who is respected and considered for his credibility, capability and thoroughness in the field of hadith. The majority of hadith books used by muslim community today is the result of albani’s takhrij, tahqiq and ta’liq. However, albani is also led to criticism over his inconsistency to judge hadith in the works of classical ulama such as bukhari, muslim, and other four sunan books.